Propuesta de un diseño de sistema de redes de distribución de gas natural doméstico para la vereda San Roque y zonas aledañas al campo Cerro Gordo, en el departamento del Norte de Santander (2021)
Since the inhabitants of San Roque have presented the need to acquire the GN service and the Wattle Petroleum company wants to reduce the social gap and strengthen the existing relationships of trust with the community, this document studies a possible scenario that provides a solution to the problem raised by developing the design of a natural gas distribution network, which consists of a virtual system and the subsequent distribution network that satisfies the consumption of both the inhabitants of the populated center and the rural area.